Measuring ligand concentration where it matters: Assessing the “micro pharmacokinetic/pharmacodynamics” of adenosine receptor ligands - Lochray, Jack (2022)
The methods used to determine fundamental pharmacological parameters almost exclusively assume that the concentration of drug in the local environment of the target receptor is equal to the concentration of drug that has been added to the system. It has, however, recently been shown that, dependent upon their physiochemical properties, β2-adrenoceptor ligands can interact directly with phospholipids, increasing their local concentration and directly influencing the measured association rate constant at the receptor. This local concentrating effect also been demonstrated directly using a fluorescent β2-ligand with fluorescence correlation spectroscopy (FCS).